An integration of art education into preschool instruction - Hana Stadlerová (Problemy Wczesnej Edukacji)
The present paper describes the educational possibilities of art activities in preschool education which correspond to the contemporary priorities of preschool instruction. It presents the goals and aims of some action research which was conducted in kindergartens. Through non-traditional art activity, the educational opportunities were examined, focusing on an analysis of their procedures; reflections on individual activities being carried out. The research results were designed to help bring about real changes in kindergartens, to document the contribution of art creation and to provide arguments for personality-oriented education in preschool instruction.